Anti-glycation and phytochemical properties of cinnamon stem-bark water extract - Adeniran, Oluwaseyefunmi Iyabo; Sethoga, Lesibana Samuel; Shai, Leshweni Jeremia; Gololo, Sechene Stanley (Asian Journal of Chemistry, 2023)
The study evaluated the ability of cinnamon stem-bark water extract (CWE) to break established cross-links formed between proteins and advanced glycation end-products (AGEs) as well as its anti-glycation effect. The extract showed a dose-dependent anti-glycation effect against total fluorescent AGEs (FAGEs) derived from both glucose and fructose. CWE recorded a uniform IC50 value of 0.13 mg/mL for both glucose and fructose-derived FAGEs while aminoguanidine, a well-known synthetic anti-glycative agent gave IC50 values of 0.14 mg/mL for the glucose and 0.17 mg/mL for the fructose derived FAGEs. The anti-glycative effect of CWE was also significantly higher than aminoguanidine against total immunogenic AGE (TIAGEs) in both sugar models (p < 0.001). While CWE and aminoguanidine showed weak protein cross-link breaking activity selectively on fructose-derived protein cross-links already formed, none whatsoever was detected exerted on the established glucose-derived protein cross-links. Phytochemical screening revealed the presence of several important secondary metabolites which may have contributed to the anti-glycative effect of CWE. Gas chromatography mass spectrometry enabled the identification of (+)-alpha-tocopherol acetate, a chain breaker, in the methanol fraction of CWE. Although CWE showed great potential for inhibition of formation of major types of AGEs, it appears to be poor in breaking established cross-links formed between proteins and AGEs.